2008
DOI: 10.2298/bah0804139g
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tribulus terrestris extract on semen quality and serum total cholesterol content in White Plymouth Rock-mini cocks

Abstract: Tribulus terrestris extract was added to the water of 10 cocks from the population White Plymouth Rock-mini cocks once daily in dose 10mg/kg body weight for a period of 11weeks. The trial lasted 20 weeks-1week preparatory and 19 weeks experimental period. Eight weeks of the experimental period were intended to measure the aftereffect of the tested product. It was found, that Tribulus terrestris extract improves cocks semen quality : volume of ejaculate, spermatozoids concentration and motility, and shortened t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 7 publications
0
15
0
2
Order By: Relevance
“…The biologically active substances of VemoHerb T are: steroidal saponins of furostanol type determined as protodioscin (55 to 65%); dubbing substances, calculated as tanin (not more than 10%); flavonoids, determined as rutin (not more than 10%).The qualitative indices of this product are controlled in accordance with company documentation [17]. TT extract improves the reproductive functions [4,7], productivity [17,18] and health [5,14] in animals.Our earlier studies demonstrated positive effect of VemoherbT addition on the laying capacity and egg quality in hens [2,3] and Guinea fowls [12]. To our knowledge there are no information regarding the effect of TT supplementation on this parameters in quails.…”
Section: Introductionmentioning
confidence: 99%
“…The biologically active substances of VemoHerb T are: steroidal saponins of furostanol type determined as protodioscin (55 to 65%); dubbing substances, calculated as tanin (not more than 10%); flavonoids, determined as rutin (not more than 10%).The qualitative indices of this product are controlled in accordance with company documentation [17]. TT extract improves the reproductive functions [4,7], productivity [17,18] and health [5,14] in animals.Our earlier studies demonstrated positive effect of VemoherbT addition on the laying capacity and egg quality in hens [2,3] and Guinea fowls [12]. To our knowledge there are no information regarding the effect of TT supplementation on this parameters in quails.…”
Section: Introductionmentioning
confidence: 99%
“…It has been, however, suggested that carvacrol exhibit antioxidant activity and inhibit key enzymes in cholesterol and lipid synthesis (Qureshi et al 1983;Elson and Qureshi 1995;Crowell 1999), the roles which have no interrelation with AA metabolic pathways. On the other hand, many clinical investigations have showed that carvacrol containing herbal extracts are able to alter reproductive functions in animals through affecting sex hormones secretion and their physiological balance (Dehghani et al 2008;Grigorova et al 2008), a concept which detailed by Khosravinia (2015) resulting in the idea of "anabolic steroids-elevating effect for carvacrol", again a physiological fact with no direct connection with AA metabolism and roles.…”
Section: Discussionmentioning
confidence: 99%
“…This is expectable due to its hypoglicemic and hypocholesteromic effects of TT. However, there has been a contradiction between blood parameters and the biochemical effects of TT 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…TT extract decreased serum glucose level in Brown Lohman hens 17 and decreased serum cholesterol level in guinea fowl 18 , while increased reproductive performance in White Plymouth Rock-mini cocks 19 . Dietary TT extract (60 and 120 ppm, Ultimate Nutrition) did not decrease growh performance of broiler chicks when given to broiler chicks in commercial diet for 21 days suggesting that the higher TT dose trials are needed 20 .…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation